The microstructure and mechanical properties of titanium/copper welded joint by FSW. Issue 17 (22nd November 2022) - Li, Jie; Zhou, Peng; Wei, Guijiang; Huang, Jiankang; Shi, Hongyuan
Abstract : The dissimilar metal of Ti6Al4V and T2 were joined using a butt joint with and without an intermediate layer Ag by friction stir welding. The interfacial Ti–Cu IMCs of both joints are composed of Ti2 Cu, TiCu and Ti3 Cu4, and the thicknesses are about 1.5 μm and 3 μm, respectively. The intermediate layer Ag can promote the diffusion of Ti to Cu side, and the diffusion of Ti elements plays a dominant role in the formation of Ti–Cu IMCs. The joint with the intermediate layer Ag presents a higher tensile strength, which is about 70% of the Cu base metal. The fracture characteristics of both types of the joints are brittle fracture, but the tensile fracture regions are different.